Prevalence of Burn in children under (15) years in Mosul City (2009, 2010) - Radwan H. Ibraim; Hanady J. Mahmood; Habis A. Salih (Kufa Journal for Nursing Sciences)
Objective: The aim of present statistical study resumption to appear extent prevalence of burn in children under 15 years in Mosul city.